Development of Eggshell Powder Potential in Claypot for Water Filtration Process for Rural Dwellers in Nigeria - Abdulhameed Umar Abubakar; Aliyu Idris; Emmanuel W. Gadzama; Hijab A. Mahmoud (Journal of Advanced Industrial Technology and Application, 2024)
Access to safe and clean drinking-water in the rural areas of Nigeria is practically impossible, because they are limited to such sources as streams, rivers, hand dug wells and rare cases boreholes which are poorly managed, leading to several health complications. Contaminated water contributes largely to the number of reported health related issues in rural communities of developing countries. Consumption of water contaminated by disease-causing pathogens can cause health problems such as diarrhea, cholera, typhoid, dysentery, and skin diseases. This project attempts to provide a low-cost and environmentally friendly efficient method of water filtration process using clay minerals reinforced with a filter material - eggshell. This was achieved through the characterization of the clay and eggshell materials, the preparation of the clay – eggshell blend mix at 1:1, 1:2 and 2:1 and the construction of prototype clay – eggshell blend pot. The use of clay and eggshell as the adsorption materials offer great advantages, because it is readily available, cheap and practicable.